In silico identification of linear B-cell epitope in Coronavirus 2019 (SARS-CoV-2) surface glycoprotein: A prospective towards peptide vaccine - Singh P.; Tripathi M.K.; Shrivastava R. (My University, 2025)
BACKGROUND: The 2020 Coronavirus pandemic continuing spread of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS CoV-2). At the moment, there is no specific antiviral treatment or monoclonal antibodies or vaccines available for COVID-19. SARS-CoV-2 is positive-stranded RNA viruses with a crown-like appearance due to the occurrence of spike (surface) glycoproteins on the envelope. In the present study, the computational method used to predict the significant linear B cell epitopes of SARSCoV-2 surface glycoprotein. METHODS: FASTA sequence of SARS-CoV-2 surface glycoprotein was retrieved from the NCBI database, and further its primary and secondary structure was analyzed for its physical and chemicals properties. IEDB server was used to predict the B-cell epitopes. RESULTS: ABCprep server and IEDB server prediction results for B-cell epitopes showed 16 and 21 linear epitope sequences respectively in the surface glycoprotein of SARS-CoV-2. CONCLUSIONS: Obtained results conclude that predicted B-cell Epitopes may serve as an immunogen for eliciting monoclonal antibodies which can be used as a potential candidate for the treatment or diagnostic purpose for COVID-19. © 2021 Minerva Biotechnology and Biomolecular Research. All rights reserved.